Reproductive Biology of Rheum webbianum Royle, a Vulnerable Medicinal Herb From Alpines of North-Western Himalaya - Wani, Ishfaq Ahmad; Verma, Susheel; Ahmad, Parvaiz; El-Serehy, Hamed A.; Hashim, Maha J. (Frontiers in Plant Science, 2022)
Information on reproductive biology and pollination ecology studies of threatened plants are essential to develop strategies for their sustainable utilization and effective conservation. As such, these studies were conducted on Rheum webbianum, a high value “vulnerable” medicinal herb of the north-western Himalaya. This species presents a unique mode of reproductive behavior through the involvement of different floral events, including the movement of reproductive organs. The plants survive extreme cold conditions through underground perennating rhizomes that sprout into juvenile shoots with the onset of the favorable climatic conditions. The peduncle arises from the axils of the radical leaves, bearing a globular collection of densely arranged hermaphrodite flowers with temporally separated male and female phases; the male phase precedes the female phase (protandry). Anther dehiscence and stigma receptivity is post anthesis. Anthers dehisce longitudinally along margins, liberating a large mass of spherical and tricolpate pollen with spinulose exine. Pollen viability decreased to < 10% on day 9. Pistil is tristylous, each style terminating into a fan shaped stigma lobe. The pollen receptive surface of each stigmatic lobe remains incurved at an angle of 360° and shows upward movement after anthesis, forming a funnel-like structure at an angle of 180° with respect to the ovary. Flowers are both insect as well as wind pollinated. Pollination syndrome is ambophilous. Spontaneous autogamy or geitonogamy to certain extent is achieved in this species due to arrangement of flowers in the inflorescence and overlapping of male and female reproductive phases among them. Incurved stigmatic lobes and outward movement of stamens facilitate outcrossing. Pollen/ovule ratio estimates, results of pollination experiments on breeding behavior, outcrossing and self-compatibility indices demonstrated that plants are self-compatible and cross fertile.